SOSIALISASI MOTIVASI BERWIRAUSAHA BAGI IBU-IBU PKK RW 010 SUNTER AGUNG KOTA JAKARTA UTARA - Ana Chaerunisyah; Alfirahmi Alfirahmi; Tri Waluyo Prehantio; Annisa Nur Khasanah; Ines Karinastiti (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The program for the Development of Family Welfare through the Empowerment of PKK Mothers (PKM PKK Mothers) in RW 010 Sunter Agung, North Jakarta, stands as a milestone initiative to enhance the well-being of families and communities. Focused on improving the knowledge and skills of PKK mothers, the program encompasses aspects of life involving financial management, health, education, and the development of micro-enterprises. The primary objective is to provide entrepreneurship motivation to PKK mothers, with the hope of increasing interest in the business world, particularly through the introduction of banana chips products by students from the STIAMI Institute. Socialization is conducted through engaging direct approaches. Through a series of training activities, socialization, and micro-enterprise development, this program not only enhances entrepreneurial skills but also aims to unearth the potential of PKK mothers in creating job opportunities at the community level. The results of the socialization indicate that PKK mothers have started their own businesses, but socialization is essential to understand sales methods and encourage proactive, creative, and risk-taking attitudes. In conclusion, the PKM PKK Mothers program is capable of providing entrepreneurial encouragement, developing potential, and opening economic opportunities through training, collaboration, and product innovation